Elaboración y validación de una escala de motivación y estrategias de aprendizaje para escolares de quinto y sexto grado de primaria - Aliaga Tovar, Jaime (2002)
Based in the model of Printrich and DeGrott (1990) and in spanish studies by Roces et al (1999), it has been elaborated a Motivation and Strategy of learning Scale to be used in third cycle of elementary school. The sample was ran¬dom and composed by 1215 students proportionally distributed according to kind of school (Public/private), sex and grade of studies (5th or 6th) of elementary school. The questionnaire has 2 sections, motivation and strategy of learning, each one with 6 scales. Its internal structure is evaluated by factor exploratory analysis with principal components and varimax rotation. This analysis along with item test correlations made possible to eliminate defective items and purifi the scales, which show psychometrically appropriate validity and reliability indexes, making of it an useful tool for the valuation of the referred variables.